Optimasi Parametrik Minyak Pirolisis dan Karbon Sisa Hasil Pirolisis Ban Bekas dalam Reaktor Atmosfer Inert. - Mangalla, Lukas Kano; Lolok, Agustinus; Samhuddin, Samhuddin; Barata, La Ode Ahmad (Piston: Jurnal Teknologi, 2025)
Waste tires represent a significant environmental challenge that requires sustainable solutions through conversion into energy. One of the waste treatment technologies involves a pyrolysis process that converts solid waste into liquid fuels and solid material for backfill. This study aims to optimize the process parameters for the pyrolysis of waste tires in an inert atmosphere reactor to maximize the yield and quality of liquid and solid products. Experiments were conducted by varying temperature (400, 450, 500°C) and residence time (10, 15, 20 minutes) using controlled cubic-shaped tire samples. The results indicate that the optimal operating conditions were achieved at 450°C and 15 minutes, producing a pyrolysis oil yield of 48.3% with a high calorific value of 44.6 MJ/kg, along with a solid char yield of 35.2%. he produced solid char has potential applications as a filler material in civil construction materials. Further analysis revealed significant energy conversion efficiency of the process. These findings provide a strong technical foundation for developing commercial-scale pyrolysis technology that effectively manages tire waste while producing quality alternative fuels